PENGARUH KEPUASAN INFORMASI TERHADAP KEPUASAN MEMILIH PERGURUAN TINGGI - Raden Sudarwo; Anfas Anfas; Irfandi Buamonabot (P3M STIEM BONGAYA, 2018)
The purpose of this study is to determine and examine the effect ofinformation satisfaction on choosing a college. Respondents in this study were studentsof the Ternate Open University Distance Learning Unit Program. A total of 74respondents from the survey. Data analysis is done using simple regression. The resultsshowed that information satisfaction had a positive effect on the satisfaction of choosinga college.